Pulsed injector of the working substance for magnetoplasma compressor - Staltsov, V.V. (Вопросы атомной науки и техники, 2015)
Technical description of the high-speed pulsed injector of working substance with a radial gas supply for magnetoplasma compressor is given. The results of studies on the main gas-dynamic and electrotechnical characteristics of the gas injector are presented. Наведено технічний опис швидкодіючого імпульсного інжектора робочої речовини з радіальним поданням газу для магнітоплазмового компресора. Наведено результати досліджень основних газодинамічних та електротехнічних характеристик газового інжектора. Приведено техническое описание быстродействующего импульсного инжектора рабочего вещества с радиальной подачей газа для магнитоплазменного компрессора. Приведены результаты исследований основных газодинамических и электротехнических характеристик газового инжектора.